(untitled) (Bangkok, 2012)
This book includes many sessions: decade of development, growth, and impacts 2001 - 2010 in the GMS, food - water - energy nexus, challenges and dynamics of growth in the next decade 2011 - 2020, responses to challenges of the next decade in the GMS.
Keywords: Economic growth,Environmental policy,Tăng trưởng kinh tế,Chính sách môi trường